2020
DOI: 10.1101/cshperspect.a036137
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Role of PTEN in Insulin Signaling and Resistance

Abstract: PDK that promotes GLUT4 translocation to the plasma membrane of skeletal muscles. Alternatively, IRS phosphorylates and activates the GRB2/SHC/SOS pathway, which promotes the phosphorylation of Ras-GDP to Ras-GTP. Ras-GTP ultimately activates ERK1/2, which mediates GLUT4 transcription and cellular proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 122 publications
(131 reference statements)
1
27
0
Order By: Relevance
“…47 This pathway is also a very important signaling pathway for regulating glucose homeostasis and its activation can reduce circulating glucose concentration. 48 A relatively higher activity of PI3K-Akt pathway in cases compared to controls can potentially induce a metabolic phenotype similar with that observed in the present study, that is, higher lipids (possibly because of higher endogenous biosynthesis) and uric acids (because of lower urinary excretion) and lower glucose in fasting plasma. Higher activity of PI3K-Akt singling is also etiologically important in the development of PCa.…”
Section: Other Studiessupporting
confidence: 81%
“…47 This pathway is also a very important signaling pathway for regulating glucose homeostasis and its activation can reduce circulating glucose concentration. 48 A relatively higher activity of PI3K-Akt pathway in cases compared to controls can potentially induce a metabolic phenotype similar with that observed in the present study, that is, higher lipids (possibly because of higher endogenous biosynthesis) and uric acids (because of lower urinary excretion) and lower glucose in fasting plasma. Higher activity of PI3K-Akt singling is also etiologically important in the development of PCa.…”
Section: Other Studiessupporting
confidence: 81%
“…IR always involves disturbances in intracellular insulin signaling [92]. It commonly concerns decreased activity or expression of molecules involved in signal transduction (INSR, IRS-1, GLUT-4), decreased expression / translocation of GLUT-4, or increased expression/activity of antagonists of PI3K/AKT pathway, e.g., phosphatase and tensin homolog (PTEN), and polypyrimidine tract binding protein-1 (PTP1B) [93][94][95][96]. The impaired signaling of insulin demands increased concentrations of insulin (hyperinsulinemia).…”
Section: Insulin Resistance Hyperglycemia and Oxidative Stressmentioning
confidence: 99%
“…The findings showed that PTEN exhibited similar changes to those of G6PC2 following the administration of differentially sourced exosomes. Studies report that PTEN impairs insulin signaling and induces insulin resistance during the pathogenesis of type 2 diabetes [ 49 ]. Metabolic organs, including the liver and muscle, exhibit significant increase in insulin sensitivity and glucose metabolism after the knockout of PTEN [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%